Physiologic performance test differences in female volleyball athletes by competition level and player position - Schaal, M.; Ransdell, L. B.; Simonson, S. R.; Gao, Y. (The Journal of Strength and Conditioning Research, 2013)
The purpose of this study was to examine physiologic performance test differences by competition level (high school and Division-I collegiate athletes) and player position (hitter, setter, defensive specialist) in 4 volleyball-related tests. A secondary purpose was to establish whether a 150-yd shuttle could be used as a field test to assess anaerobic capacity. Female participants from 4 varsity high school volleyball teams (n = 27) and 2 Division-I collegiate volleyball teams (n = 26) were recruited for the study. Participants completed 4 performance-based field tests (vertical jump, agility T-test, and 150- and 300-yd shuttle runs) after completing a standardized dynamic warm-up. A 2-way multivariate analysis of variance with Bonferroni post hoc adjustments (when appropriate) and effect sizes were used for the analyses. The most important findings of this study were that (a) college volleyball athletes were older, heavier, and taller than high school athletes; (b) high school athletes had performance deficiencies in vertical jump/lower-body power, agility, and anaerobic fitness; (c) lower-body power was the only statistically significant difference in the performance test measures by player position; and (d) the correlation between the 150- and 300-yd shuttle was moderate (r = 0.488). Female high school volleyball players may enhance their ability to play collegiate volleyball by improving their vertical jump, lower-body power, agility, and anaerobic fitness. Furthermore, all player positions should emphasize lower-body power conditioning. These physical test scores provide baseline performance scores that should help strength and conditioning coaches create programs that will address deficits in female volleyball player performance, especially as they transition from high school to college.